Cognition in crisis management teams: an integrative analysis of definitions. Issue 10 (2nd October 2020) - Moon, Jukrin; Sasangohar, Farzan; Son, Changwon; Peres, S. Camille
Abstract: In large-scale extreme events, multidisciplinary crisis management teams (CMTs) are required to function together cognitively. Despite theoretical maturity in team cognition and recurrent emphasis on cognition in the crisis management practices, no synthesis of theoretical and practical discourses is currently available, limiting empirical investigations of cognition in CMTs. To address this gap, this paper aims to review the definitions of cognition in CMTs, with a particular focus on examining if and to what extent they are diversified. Through a systematic process to search peer-reviewed journal articles published in English from 1990 to 2019, 59 articles were selected with 62 coded definitions of 11 different constructs. The similarities and variabilities of the definitions were examined in terms of their theoretical and practical emphases and then synthesised into an integrative definition expected to serve as a general guide of reference for future researchers seeking an operational definition of cognition in CMTs. Practitioner summary: Understanding of cognition in CMTs is grounded in various theories and models with varying assumptions. An integrative conceptualisation of such cognition as interaction within and across CMTs to perceive, diagnose, and adapt to the crisis may facilitate the accumulation of knowledge and future operationalisations. Abbreviations: CMT(s): crisis management team(s); SMM: shared mental model; TMM: team mental model; COP: common operating picture; SSA: shared situation awareness; TSA: team situation awareness; DC: distributed cognition; ITC: interactive team cognition; TMS: transitive memory system(s); DSA: distributed situation awareness